The predictive role of CA-125 in the management of tubo-ovarian abscess. A retrospective study. (July 2019) - Levin, Gabriel; Herzberg, Shmuel; Dior, Uri P.; Shushan, Asher; Gilad, Ronit; Benshushan, Avi; Rottenstreich, Amihai
Abstract: Objective: Tubo-ovarian abscess (TOA) is a well-established sequel of acute pelvic inflammatory disease (PID). While as up to 25% of women will experience conservative treatment failure, the factors associated with treatment failure are not clearly-established, and the role of Cancer antigen 125 (CA-125) is under-studied. We aim to evaluate the role of CA-125 in the conservative management of TOA. Study design: A retrospective cohort study conducted at tertiary university-afﬁliated hospital during 2007-2018. Ninety one patients were diagnosed with a TOA and underwent a trial of conservative management with intravenous antibiotics. Patients who eventually underwent surgical intervention were compared with patients managed conservatively. Results: Overall, 39/91 (42.8%) underwent an invasive intervention subsequent to failed antibiotic treatment. Patients who experienced conservative treatment failure had higher medians of inflammatory markers as CRP (15.7 vs. 10.8 mg/L, p = 0.02), WBC count (14.2 vs. 12.4 1, 000/mm 3, p = 0.04) and platelet count (374 vs. 295 10 9 /L, p = 0.04) at admission. Higher levels of CA-125 at admission were found in those who required an invasive intervention (57 vs. 30 U, p = 0.02) as well. The largest diameter of TOA at admission was higher in those who required an invasive intervention as compared to those who were successfully treated conservatively (75 mm vs. 57 mm, p = 0.01). CA-125 level was found to be the only independent factor associated with conservative treatment failure (OR; 95% conﬁdence interval [CI], 1.27, 1.08–1.48, p = 0.03). Conclusion: Elevated CA-125 serum levels were found to be associated with failure of conservative parenteral antibiotic therapy for TOA. This finding should be better evaluated in a prospective manner.